EDITORIAL - Goh, Pauline Swee Choo; Ratnavadivel, Nagendralingan (Journal of Research, Policy & Practice of Teachers and Teacher Education, 2018)
It is our pleasure to present the new issue of Journal of Research, Policy & Practice of Teachers & Teacher Education (JRPPTTE). The Editorial Board has worked thoughtfully to assemble a differentiated and pertinent publications about education and all that it encompasses. This issue highlights many topics tied together by the growing interest worldwide, be it in teacher education, higher education or education in schools - in upholding quality in education. Each article takes for its author or subject a different aspects of education, but each sets out to advance some facets of educational quality, and more specifically, quality in teaching and learning.